Fostering holistic natural-risk resilience in spatial planning: Earthquake events, cultural heritage and communities - Bojanić Obad Šćitaroci, Bojana; Pierantoni, Ilenia; Sargolini, Massimo; Sopina, Ana (TeMA - Journal of Land Use, Mobility and Environment, 2021)
Natural disasters cause destruction of (land/urban)scape values and cultural heritage, social and cultural ties, and have direct impact on spatial resources that appeal to spatial planning from a perspective of enhancing present resilience and reducing future risks. The research aim is to build a knowledge framework on integrating perspectives of natural-risk resilience - natural risk, cultural heritage, communities, spatial resources and spatial planning, tested on research cases of earthquake affected areas in Italy and Croatia. The Heritage Urbanism approach is applied in comparison of Central Italy disaster experience and tendencies in the Croatian capital of Zagreb, providing identity factors and evaluation criteria that assist in reading existing resilience models and forming new models. Interrelation structures of (land/urban)scape resilience dimensions and models of natural-risk resilience contribute to enhancing risks-reduction and resilience in urban planning at high-risk exposure. Achieving holistic natural-risk resilience is possible when (land/urban)scape, cultural, identity, social, spatial, planning, economic resilience models are integrated in a way that they benefit from each other. Spatial planning responses to natural disasters that affect cultural and (land/urban)scape heritage, and spatial resources that have to be planned in close interaction with local communities to improve preparedness and prevent destruction, damage, and loss of collective memory, tradition, and identity.